2020
DOI: 10.1097/prs.0000000000007343
|View full text |Cite
|
Sign up to set email alerts
|

Shear Force Processing of Lipoaspirates for Stem Cell Enrichment Does Not Affect Secretome of Human Cells Detected by Mass Spectrometry In Vitro

Abstract: Background: Lipofilling is one of the most often performed surgical procedures in plastic and reconstructive surgery. Lipoaspirates provide a ready source of stem cells and secreted factors that contribute to neoangiogenesis and fat graft survival. However, the regulations about the enrichment of these beneficial cells and factors are ambiguous. In this study, the authors tested whether a combination of centrifugation and homogenization allowed the enrichment of viable stem cells in lipoaspirates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The significance of this observation, however, may be undermined by a relatively small study population. In vitro studies demonstrated that similar modifications increase AD-MSC output [33,[38][39][40][41] without affecting the composition of secreted proteins [41].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this observation, however, may be undermined by a relatively small study population. In vitro studies demonstrated that similar modifications increase AD-MSC output [33,[38][39][40][41] without affecting the composition of secreted proteins [41].…”
Section: Discussionmentioning
confidence: 99%
“…There have also been apprehensions that mechanical processing might affect the genome and therefore protein synthesis in adipose cells. An analysis of cells in lipoaspirate after mechanical processing showed that mechanical processing does not affect the secretome of autologous adipose cells and can therefore be used safely in a multivariety of surgical settings [ 37 ]. On top, the authors managed to show that mechanical processing was able to boost the cellular fraction in comparison to nonprocessed lipoaspirate.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, ASCs contribute to fat graft survival not only by their proliferative capacities but also by paracrine angiogenic properties [ 9 , 41 ]. Therefore, enrichment of lipoaspirate with ASCs is intensively investigated by numerous groups [ 36 , 42 , 43 , 44 , 45 , 46 ]. Safety concerns regarding enzymatic digestion of fat tissue have led to an increasing recognition of methods that circumvent the risks of enzymatic digestion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%